Gender and Dark Personality Traits as Determinants of Collective Action Participation: A View from Croatia - Tomislav Pavlović (Anali Hrvatskog Politološkog Društva)
This study is focused on multiple aims. The first goal is to extend the evidence base and offer insights into patterns of attitudes and intentions related to activism (normative collective actions) and radicalism (non-normative and violent collective actions) among youth in Croatia. The second goal is to test the "dark-ego-vehicle" principle by evaluating whether the profiles based on the patterns of attitudes and intentions related to collective actions significantly differ with respect to the general dark personality trait. Data of 727 Croatian university students (53% women) were analyzed using latent profile analysis, which revealed four profiles in male and five profiles in female subsample. Most profiles (passive, activists, moderate radicals, strong radicals) were established among men and women, with negligible differences in indicator means. However, men were more likely to be categorized as moderate radicals (and slightly more likely to be categorized as passive), while women were more likely to be categorized as activists. The study partially supported the "dark-ego-vehicle" principle among women: while activists scored low on the general dark personality trait, moderate and strong radicals exhibited elevated scores. Among men, activists also scored low on dark personality trait, unlike passive individuals, moderate and strong radicals.